2017
DOI: 10.3389/fmed.2017.00235
|View full text |Cite
|
Sign up to set email alerts
|

The Amide Local Anesthetic Lidocaine in Cancer Surgery—Potential Antimetastatic Effects and Preservation of Immune Cell Function? A Narrative Review

Abstract: Surgical removal of the primary tumor in solid cancer is an essential component of the treatment. However, the perioperative period can paradoxically lead to an increased risk of cancer recurrence. A bimodal dynamics for early-stage breast cancer recurrence suggests a tumor dormancy-based model with a mastectomy-driven acceleration of the metastatic process and a crucial role of the immunosuppressive state during the perioperative period. Recent evidence suggests that anesthesia could also influence the progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 102 publications
2
54
0
3
Order By: Relevance
“…Amide local anesthetics act on nerve cells by blocking voltage-gated sodium channels, resulting in decreased depolarization and repolarization rates of excitatory nerve cell membranes [30,31]. It has been shown that common amide linked local anesthetics exhibit anticancer activity in a variety of cancers, including lung cancer, hepatocellular carcinoma, and thyroid cancer [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Amide local anesthetics act on nerve cells by blocking voltage-gated sodium channels, resulting in decreased depolarization and repolarization rates of excitatory nerve cell membranes [30,31]. It has been shown that common amide linked local anesthetics exhibit anticancer activity in a variety of cancers, including lung cancer, hepatocellular carcinoma, and thyroid cancer [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrate beneficial effects of the amide-linked local anesthetic ropivacaine on AR 5 days after allogeneic lung transplantation in mice. Amide-linked local anesthetics such as ropivacaine and lidocaine have been demonstrated to possess profound anti-inflammatory properties [12][13][14]. As inflammatory signaling processes, leukocyte infiltration and subsequent damage to the transplanted organ are hallmarks of AR, we hypothesized that the drug would also be able to attenuate AR due to its antiinflammatory effects, e.g., by preserving endothelial barrier function [6].…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is an ideal adjuvant drug for cancer treatment given its major therapeutic advantages, strong anti-inflammatory effects, and protective effects on innate immune system surveillance. 91,92 In addition, it improves the prognosis of patients with cancer. However, its use in patients with cancer warrants further clarifications and clinical validation.…”
Section: Local Anesthetic Agentsmentioning
confidence: 99%
“…Moreover, regional anesthesia does not affect CMI and reduces surgeryinduced neuroendocrine response by weakening afferent nerve conduction in the HPA axis and the sympathetic nervous system. 85,91,104 Therefore, reducing opioid usage and inhaled anesthetic agents may reduce the risk of tumor recurrence.…”
Section: Anesthesia-related Factors and Cancer Recurrence And Metastasismentioning
confidence: 99%